CARS-imaging guidance for fs-laser ablation precision surgery - Meyer, Tobias; Ackermann, Roland; Kammel, Robert; Schmitt, Michael; Nolte, Stefan; Tuennermann, Andreas; Popp, Jürgen (Analyst, 2019)
Due to ageing populations the number of tumors is increasing worldwide. Successful surgical treatment requires complete resection of tumors to reduce recurrence rates. To reach this goal, novel methods combining in vivo tumor and tumor margin detection with low invasive precision surgical tools are needed. Coherent anti-Stokes Raman scattering (CARS) imaging is a highly promising optical tool for visualizing tumors based on characteristic changes in tissue morphology and molecular composition, while fs-laser ablation is to date the most precise surgical tool established in ophthalmology. In this contribution, CARS imaging has been combined with fs-laser ablation as a new approach for image-guided precision surgery for the first time. CARS guided fs-ablation has been applied to ablate brain, liver, skin, muscular and vascular tissues with μm-precision using sub-100 fs pulses of μJ level. We demonstrate superior imaging performance and contrast as well as detection of tissue margins by coherent Raman microscopy in comparison to laser reflectance imaging. The combination of CARS-image-guided tissue ablation is a promising tool for minimally invasive surgeries particularly in the vicinity of functional structures in the future.
CRIS-Team Scopus Importer:2023-04-20